Formal System Verification State-of the-Art and Future Trends - Drechsler, Rolf.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book provides readers with a comprehensive introduction to the formal verification of hardware and software. World-leading experts from the domain of formal proof techniques show the latest developments starting from electronic system level (ESL) descriptions down to the register transfer level (RTL). The authors demonstrate at different abstraction layers how formal methods can help to ensure functional correctness. Coverage includes the latest academic research results, as well as descriptions of industrial tools and case studies. Provides latest results on formal methods along the complete design flow; Covers different abstraction layers, from ESL to RTL; Addresses formal verification in both digital and analog contexts; Demonstrates techniques in current industrial use.
Formal Techniques for Verification and Coverage Analysis of Analog Systems -- Verification of Incomplete Designs -- Probabilistic Model Checking: Advances and Applications -- Software in a Hardware View -- Formal Verification - The Industrial Perspective.
Keywords: Electronic circuits; Microprocessors; Computer architecture; Electronics; Electronic Circuits and Systems; Processor Architectures; Electronics and Microelectronics, Instrumentation